2020
DOI: 10.3390/cancers12082267
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of Incidental Deep Vein Thrombosis in Patients with Cancer Presenting with Incidental Pulmonary Embolism

Abstract: In symptomatic acute pulmonary embolism (PE), the presence of deep vein thrombosis (DVT) is a risk factor for 30- and 90-day mortality. In patients with cancer and incidental PE, the prognostic effect of concomitant incidental DVT is unknown. In this retrospective study, we examined the effect of incidental DVT on all-cause mortality in such patients. Adjusted Cox multivariate regression analysis was used for relevant covariates. From January 2010 to March 2018, we included 200 patients (mean age, 65.3 ± 12.4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Malignancy by itself is a main risk factor for the development of VTE, but cancer patients have multiple other clinical risk factors, including chemotherapy, multiple surgeries, and immobility [ 16 , 31 , 32 , 33 , 34 ]. Despite being unsuspected or incidentally discovered, incidental VTEs appear to be a substantial risk for cancer patients, and this may influence patient morbidity and mortality [ 14 , 27 , 30 ]. In the current study, we used data collected from cancer patients presenting to our comprehensive cancer center over a 10-year period to characterize C-DVT in cancer patients presenting with unsuspected PE, describing the outcomes of patients with these events.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malignancy by itself is a main risk factor for the development of VTE, but cancer patients have multiple other clinical risk factors, including chemotherapy, multiple surgeries, and immobility [ 16 , 31 , 32 , 33 , 34 ]. Despite being unsuspected or incidentally discovered, incidental VTEs appear to be a substantial risk for cancer patients, and this may influence patient morbidity and mortality [ 14 , 27 , 30 ]. In the current study, we used data collected from cancer patients presenting to our comprehensive cancer center over a 10-year period to characterize C-DVT in cancer patients presenting with unsuspected PE, describing the outcomes of patients with these events.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies for suspected PE have shown that concomitant DVT alters short-term mortality, and its presence can be used to improve risk stratification in patients with intermediate to low risk for short-term complications from PE [ 45 , 46 , 47 , 48 ]. A recent study by Barca-Hernando et al that included 200 cancer patients with incidental PE, of which 62 patients (31.0%) had C-DVT, concluded that the presence of C-DVT was not associated with poorer survival (univariate analysis: HR 1.09, 95% CI 0.43–2.75, p = 0.855) [ 14 ]. However, the small sample size of that study may have limited the statistical power to detect a difference in survival outcomes, and the study did not include a multivariable analysis for C-DVT, so other factors that influence survival could have masked the true impact of C-DVT on survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation